Infectious diseases in sports - Beck, C. K. (Medicine & Science in Sports & Exercise, 2000)
Participation in sports in on the increase; this article addresses the intersection of sports and infectious diseases. Some infections occur with increased incidence in sports; others have an increased impact in that setting. Addressed in this article are issues of diagnosis, prevention, and management of many of these infections. Included are skin/soft tissue infections, infections related to water exposure, viral infections, infections related to blood exposure, and vaccinations.